Banking Market Structure and Firm Productivity: Evidence from Indonesia - Muhtar muhtarr; Agista Putri Prameswari (MANAJEMEN DEWANTARA, 2022)
This paper empirically examines the impact of banking market structure on the productivity of small and medium enterprises. Arguably, the more competitive the banking industry, the more access to finance and the lower cost of borrowing. Eventually, it could lead to better performance of small and medium enterprises. We combine two different datasets which are dataset on small and medium enterprises and the dataset on banking. Finally, we end up with more than 91,000 firm-year observations. Our empirical results show that banking competition has significant effect on the performance of small and medium enterprises. More particular, we find that the less banking competition, the lower the performance of small and medium enterprises. Keywords: banking market structure, firm productivity, small and medium enterprises, Indonesia